Exploring the Impact of Brand Identity and Brand Image on Gen Z's Repurchase Intention through Customer Satisfaction in E-Commerce - Hutasuhut, Abir Yhasmin; Verinita; Besra, Eri (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research is motivated by the increasing consumption of cosmetic products among Gen Z, especially Wardah brand lip products through e-commerce platforms in Padang City. The main objective of this study is to analyze the effect of brand identity and brand image on customer satisfaction and repurchase intention, and test the role of customer satisfaction as a mediating variable. This research uses a quantitative approach with a causal research type and survey method through distributing questionnaires to 155 female Gen Z respondents who use E-commerce. The data analysis technique was carried out with Structural Equation Modeling (SEM) using SmartPLS 3.0. The results showed that brand identity has no positive and significant effect on customer satisfaction and repurchase intention and brand image has a positive and significant effect on customer satisfaction and repurchase intention. Customer satisfaction is also proven to have a significant influence on repurchase intention and only partially mediates the relationship between brand image and repurchase intention. The conclusion of this study confirms the importance of strengthening brand identity and image to increase customer satisfaction and loyalty. These findings provide strategic implications for the marketing development of local brands such as Wardah in reaching digital native consumers more effectively.